Pattern of Laryngomalacia Cases at the Ear, Nose, and Throat Outpatient Clinic of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, 2021-2022 - Stavina Dwiputri Rizky Rusuldi; Rizka Fathoni Perdana; Lynda Rossyanti; Rosydiah Rahmawati (Universitas Airlangga, 2026)
Highlights: The majority of laryngomalacia patients were between 3 and 12 months. Pneumonia was the most common clinical symptom, alongside dysphagia. Abstract Introduction: Laryngomalacia is the most frequent cause of stridor in infants and neonates. This study aimed to analyze the characteristics of patients with laryngomalacia at the Ear, Nose, and Throat (ENT) Outpatient Clinic, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, during 2021-2022. Methods: This was a descriptive retrospective study conducted at the ENT Outpatient Clinic, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2021 to 2022. The research variables included age, gender, clinical symptoms, and comorbidities. Results: Most patients were in the 3-12-month age group (38 patients, 48.1%). They were followed by the age group of <3 months (27 patients, 34.18%). Forty-six (58.22%) patients were males, while there were 33 (41.78%) female patients. The most common clinical symptom in patients was pneumonia (63 patients, 36.41%), followed by dysphagia (53 patients, 30.63%). Meanwhile, the most common comorbidities in patients were craniofacial abnormalities (34 patients, 30.35%), followed by heart defects (30 patients, 26.78%). The results showed that laryngomalacia patients were dominated by babies aged 2 months, with an average age of 8 months. Conclusion: Laryngomalacia often shows with pneumonia and dysphagia. There are several comorbidities that could worsen the laryngomalacia, such as craniofacial abnormalities, heart defects, and congenital syndromes. Laryngomalacia can manifest at several days or months. Any gender is at risk of being affected by laryngomalacia.